Sejarah dan Arsitektur Masjid Jami As-Syakirin Deli Tua Masa Kolonial - Putri, Aisyah Aura; Sari, Ajeng Priska; Nataly, Alya; Rahmadani, Tasya (IAI Nasional Laa Roiba Bogor, 2025)
The Jami As-Syakirin Mosque is the oldest mosque located in Deli Tua Village, Deli Tua District, Deli Serdang Regency, North Sumatra. Deli Tua holds many famous local historical values, such as the legend of the green princess, the legend of the gading pancur, the legend of the puntung cannon and other legends about the origins of the Karo tribe and the Malay tribe. Delitua is also suspected or predicted to have been the center of the Haru Kingdom. The Jami As-Syakirin Mosque during the colonial period was originally used as a resting place or stopover for travelers passing through the Deli Tua area. The Jami' As-Syakirin Mosque has a size of around 600 m2 for the land area and 300 m2 for the building area. Based on the research, it is said that this mosque witnessed the struggle of the Deli Tua community against the Colonial. And there are gunshot marks from the Dutch army on the pulpit which is said to have come from the Dutch army who attacked the Islamic army headquarters in Deli Tua. Therefore, this study aims to explain the history and architecture of the Jami As-Syakirin Deli Tua Mosque during the Colonial Period. This study uses a qualitative method with a descriptive approach, data is obtained through field observations by directly observing objects, interviews regarding the history and architecture of the mosque, as well as document/literature studies and articles related to the history and architecture of the Jami As-Syakirin Deli Tua Mosque during the Colonial Period.